Bayerotrochus delicatus, a new species of pleurotomariid from Yap Seamount, near Palau, Western Pacific (Gastropoda: Pleurotomariidae) - Zhang, Suping; Zhang, Shuqian; Wei, Peng (Zootaxa, 2016)
A new pleurotomariid species, Bayerotrochus delicatus sp. nov., collected from the Yap Seamount, near Palau, Western Pacific (8°51′N, 137°47′E), is described and illustrated. The generic assignment is based on morphology and molecular evidence. The new species is characterized by a small, depressed trochoid shell sculptured with delicate spiral threads and axial riblets; the shell surface is lustrous orange mottled with iridescence. The radula has a formula of R + 3 + 23 + (ca. 30) + (ca. 65) + 9. These features can separate Bayerotrochus delicatus sp. nov. from its congeners. To determine the relationships of Bayerotrochus delicatus sp. nov. with other pleurotomariids, a neighbor-joining (NJ) tree was established using available sequences of cytochrome c oxidase I gene (COI) from this study and GenBank.